HIGHER EDUCATION INSTITUTION ROLES IN DEVELOPING ENTREPRENEURIAL SKILLS AMONG BOAT OPERATORS IN COASTAL AREA - Abang Zainoren Abang Abdurahman; Lenny Yusrina Bujang Khedif; Zubaidah Bohari; Jati Kasuma Ali; Johanna Adlin Ahmad; Silverina Anabelle Kibat, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Sebuyau is a coastal fishing village located about 100km away from the main city of Kuching, Sarawak. Local communities depend on fishing activities, agriculture, small businesses, and cottage industry products as their economic resources. Sebuyau can be highlighted as one of the potential tourist attractions in Samarahan District through boat rentals to tourists for fishing and river cruise activities. Boat rental for fishing and river cruise activities is a community-based tourism (CBT) product that provides opportunities for boat operators or fishermen to engage in social entrepreneurship by using their existing boats. It is an approach to diversifying their sources of income with a lower impact on natural resources. However, to ensure a sustainable transformation, the local community needs to be given exposure, knowledge, and guidance to shift the activities of ordinary fishermen or individual boat owners to boat operators who are able to generate income from boat rental activities. Therefore, higher education institutions need to take proactive roles to assist local communities in ensuring this transformation is achievable. This article discusses the role of the higher education institution in developing entrepreneurial skills among boat operators in Sebuyau. In addition, this article also discusses the achievements of the local communities who have successfully managed their boat rental activities as a result of an approach involving the roles of higher education institutions.